'Studies will yield clues on varsity gender gap' - Mustaza, Masami; See, Roy Wei Zhi (New Straits Times, 2011)
KUALA LUMPUR: Many quarters lauded the government's initiative to implement a vocational technical based curriculum for secondary schools but suggested more studies be conducted to determine the real cause for the gender disparity in universities.